Cardioprotection for radiation-induced heart disease in breast cancer patients - Mędrek, Sabina; Rolek, Kasper; Homotnik, Jakub; Szmit, Sebastian (Frontiers in Pharmacology, 2026)
Radiotherapy is an integral part of early breast cancer treatment, when breast-conserving surgery is performed. Heart disease caused by radiotherapy can include pericardial lesions, cardiac dysfunction, valvular defects, coronary artery damage, and cardiac arrhythmias. Risk factors primarily include those related to the mean heart dose of radiation, but with the development of modern radiotherapy techniques, this problem is optimistically decreasing. However, concurrent pharmacological anticancer therapies still significantly impact the vessels and heart. The key problem, however, is pre-existing heart disease, often based on atherosclerosis or arterial hypertension. Efforts should be made to ensure that radiotherapy produces at most permissive cardiotoxicity, which will not affect the quality of life or survival. Hence, effective pharmacotherapy for primary and secondary cardioprotection is searching.